KELAYAKAN POSTER PADA SUB MATERI KONSERVASI DI KELAS X SMA SINTANG - Ismanuddin, Wari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to describe the feasibility of poster as learning media on conservation submaterial in 10th grader on senior high school using descriptive quantitative method. It poster feasibility was tested by five validators, two lectures of Biology Educational Study Program, FKIP Untan and three high school Biology teacher. This research used validation sheet as research instrument with likert scale. School partner was selected by using simple random sampling technique. Those selected school were Sepauk 1st State Senior High School, Tebelian 1st State Senior High School, and Borneo Sepauk Senior High School. There were three aspects which tested by the validators, those where format aspect, content aspect, and language aspect. As result, posters was stated as valid and feasible to be used as learning media, with validation value 3,6. Keywords: media, poster, validation.